Design of Web-Based Smart Classroom Booking System Using Waterfall Method - Suhadi Parman; Krisna Adilla Fernanda; Muhammad Fatih Khoiri Asim; Yusuf Alim Romadon; Muhammad Arif Rizky; Maemunah Halimatus Sa’diyah; Revi Injani; Ratu Billah Lingga Suci (Journal of Applied Informatics Science, 2025)
This study designs a web-based Smart Classroom Booking System using the System Development Life Cycle (SDLC) with Waterfall approach to enhance the efficiency of classroom scheduling and management in the Informatics study program. The development process covers the stages of planning, analysis, and design. The main features designed include real-time classroom availability display, automatic schedule validation to prevent conflicts, booking notifications, and a user-friendly interface. The design results consist of Use Case Diagram, Activity Diagram, Sequence Diagram, Class Diagram, User Interface Flow, and high-fidelity interface prototypes. This system is expected to minimize schedule conflicts, reduce manual administrative tasks, and create a more organized, transparent, and technology-driven academic environment when implemented in the future.